Health-Promoting Properties of Lacticaseibacillus paracasei: A Focus on Kefir Isolates and Exopolysaccharide-Producing Strains - Bengoa, Ana Agustina (2021)
Among artisanal fermented beverages, kefir (fermented milk drink) and water kefir (fermented nondairy beverage) are of special interest because their grains can be considered natural reservoirs of safe and potentially probiotic strains. In the last years, several reports on Lacticaseibacillus paracasei (formerly Lactobacillus paracasei) isolated from both artisanal fermented beverages were published focusing on their health-promoting properties. Although this is not the predominant species in kefir or water kefir, it may contribute to the health benefits associated to the consumption of the fermented beverage. Since the classification of L. paracasei has been a difficult task, the selection of an adequate method for identification, which is essential to avoid mislabeling in products, publications, and some publicly available DNA sequences, is discussed in the present work. The last findings in health promoting properties of L. paracasei and the bioactive compounds are described and compared to strains isolated from kefir, providing a special focus on exopolysaccharides as effector molecules. The knowledge of the state of the art of Lacticaseibacillus paracasei from kefir and water kefir can help to understand the contribution of these microorganisms to the health benefits of artisanal beverages as well as to discover new probiotic strains for applications in food industry.